The first Thanksgiving - Hayward, Linda; Watling, James (New York : Random House, 1990)
Describes how the first Thanksgiving celebration came to be.
Elem. School Library Collection, March 1998
Booklist, October 2007
Bulletin (Center for Children's books), April 2007
2.9
K-3
K-3
Keywords: Thanksgiving Day -- Juvenile literature; Pilgrims (New Plymouth Colony) -- Juvenile literature; Thanksgiving Day; Pilgrims (New Plymouth Colony); Thanksgiving Day; Pilgrims (New England colonists); Massachusetts -- History -- New Plymouth, 1620-1691 -- Juvenile literature; Massachusetts -- History -- New Plymouth, 1620-1691.; Massachusetts -- History; Readers (Elementary)